Model Keadilan dalam Penilaian Kinerja Mahasiswa sebagai Anteseden Pengaruh Komitmen pada Kinerja: Evaluasi Pembelajaran Berbasis Kompetensi - Sawitri, Hunik Sri Runing; Riani, Asri Laksmi; Cahyadin, Malik; Novela Q. A., Intan (Jurnal Aplikasi Manajemen, 2013)
This study aims to examine the importance of justice in performance assessment of learning outcome perceived by student and then foster student's  commitmentto the lecturers, so that students perform well. Research is conducted on students from various faculties in Sebelas Maret University who have experienced Competency-Based Learning. A sample of 200 students taken by stratified sampling. Confirmatory Factor Analysis (CFA) is used to test the validity of the instrument, while the Cronbach AlphaÂ  is used to test the reliability. Regression analysis is used to test the hypotheses. The results show that students'commitment to lecturers does not significantly affect the performance of the students. Similarly, when distributive justice and procedural justice controlled commitment does not significantly influence the performance of students. While procedural justice and distributive justice significantly affect the students commitment to the lecturers.